Effect of Plant Growth Regulators on growth and Yield of Brinjal at Khajura, Banke - Sharma, MD (Journal of the Institute of Agriculture and Animal Science, 2006)
A field study was conduced in split-plot design with three replications to assess the effect of plant growth regulators (PGRs) on morphological characters and yield of brinjal cvs. Pusa Purple Long (PPL) and Pusa Purple Cluster (PPC) as main plot factor at Khajura, Banke district during summer-rainy season of 2004. The sub-plot treatments composed of fresh water (control), 40 ppm NAA, 10 ppm GA3, 2 ppm 2,4-D, 300 ppm ethephon, 30 ppm BAP and 5 ppm triacontanol. The first spray was at flowering stage and the others at 20 days interval. The PGRs had no significant effect on plant height and stem diameter at the end of crop period and days to 100% plant flowering whereas the cultivars differed significantly. The PPL was earlier to 100% plant flowering, which took 33 days after transplanting. The treatments had no significant influence in fruit number per plant and fruit yield. The interaction effect showed that the. PPL did not produced statistically different fruit number per plant with respect to growth regulators, while it had significantly higher fruit yield (17.76 t/ha) at 40 ppm NAA than that at 10 ppm GA3 and 30 ppm BAP. The PPC produced significantly higher fruit number per plant and higher fruit yield (t/ha) at 30 ppm BAP than all other treatments except 5ppm triacontanol. Key words: Growth regulators, cultivar, season, marketable, unmarketable, yield J. Inst. Agric. Anim. Sci. 27:153-156 (2006)